Pengaruh Financial Literacy, Risk Perception dan Digital Trading Platform Terhadap Keputusan Investasi Generasi Z di Surabaya - Annisa Nur Rochmah; Christian Hadinata Hodianto; Lufvi Selvi Febrianti; Jeasson Oktavianus Gatur; Maria Yovita R Pardin (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of financial literacy, risk perception, and digital trading platforms on Generation Z's investment decisions. The research method used was a quantitative approach with multiple linear regression analysis based on data from 50 respondents. The results show that financial literacy has a positive and significant effect on investment decisions, with a coefficient of 1.518 and a significance level of <0.001, indicating that the higher a person's financial literacy level, the better their investment decisions. Risk perception has a negative and significant effect, with a coefficient of -0.522 and a significance level of <0.001, indicating that the higher the risk perception, the lower the tendency to invest. Meanwhile, digital trading platforms have a positive and significant effect, with a coefficient of 0.254 and a significance level of <0.001, indicating that the better the convenience and features of the digital platform, the more likely they are to make investment decisions. Overall, this regression model indicates that the combination of these three independent variables plays a significant role in shaping Generation Z's investment decisions in the digital era.